Bayesian Generalized Self Method to Estimate Scale Parameter of Invers Rayleigh Distribution - Yanuar, Ferra; Febriyuni, Rahmi; HG, Izzati Rahmi (CAUCHY, 2021)
The purposes of this study are to estimate the scale parameter of Invers Rayleigh distribution under MLE and Bayesian Generalized square error loss function (SELF). The posterior distribution is considered to use two types of prior, namely Jeffrey’s prior and exponential distribution. The proposed methods are then employed in the real data. Several criteria for the selection model are considered in order to identify the method which results in a suitable value of parameter estimated. This study found that Bayesian Generalized SELF under Jeffrey’s prior yielded better estimation values that MLE and Bayesian Generalized SELF under exponential distribution.